2019
DOI: 10.1186/s12879-019-3709-9
|View full text |Cite
|
Sign up to set email alerts
|

Cheap and rapid in-house method for direct identification of positive blood cultures by MALDI-TOF MS technology

Abstract: BackgroundRapid and accurate pathogen identification in blood cultures is very important for septic patients and has major consequences on morbidity and mortality rates. In recent years, matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF MS)-based technology has become useful for highly specific and sensitive identification of bacteria and yeasts from clinical samples including sterile body fluids. Additional in-house methods enabled direct identification from blood culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 13 publications
5
30
1
3
Order By: Relevance
“…Whilst identification had high accuracy for Gram negative bacteria as well as S. aureus and Enterococcus spp., the method performed less well for other Gram positive organisms and yeasts, consistent with other direct MALDI-TOF MS methodologies [3,[14][15][16]. The thicker cell walls and spore-forming nature of bacilli [8,[12][13][14][15][16] and the more complex processing required to disrupt yeast cell walls [19] are likely contributors. Some studies, using more complicated and costly extraction procedures, have reported slightly higher success rates for Gram positive organisms [17,18].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Whilst identification had high accuracy for Gram negative bacteria as well as S. aureus and Enterococcus spp., the method performed less well for other Gram positive organisms and yeasts, consistent with other direct MALDI-TOF MS methodologies [3,[14][15][16]. The thicker cell walls and spore-forming nature of bacilli [8,[12][13][14][15][16] and the more complex processing required to disrupt yeast cell walls [19] are likely contributors. Some studies, using more complicated and costly extraction procedures, have reported slightly higher success rates for Gram positive organisms [17,18].…”
Section: Discussionsupporting
confidence: 69%
“…The technique was inexpensive, and identification results could be obtained within 15 min of the blood culture flagging positive. Results of the in-house method were highly consistent with single colony identification for Gram-negative organisms to species and genus level (up to 99%), outperforming comparable methods in the literature which reported < 90% concordance [3,[12][13][14][15][16].…”
Section: Discussionsupporting
confidence: 67%
“…Whilst identification had high accuracy for Gram negative bacteria as well as S. aureus and Enterococcus spp., the method performed less well for other Gram positive organisms and yeasts, consistent with other direct MALDI-TOF MS methodologies [3,[14][15][16]. The thicker cell walls and sporeforming nature of bacilli [8,12,[13][14][15][16] and the more complex processing required to disrupt yeast cell walls [19] are likely contributors. Some studies, using more complicated and costly extraction procedures, have reported slightly higher success rates for Gram positive organisms [17][18].…”
Section: Discussionsupporting
confidence: 70%
“…Results of the in-house method were highly consistent with single colony identification for Gramnegative organisms to species and genus level (up to 99%), outperforming comparable methods in the literature which reported <90% concordance [3,[12][13][14][15][16].…”
Section: Discussionsupporting
confidence: 68%
“…Szerokie zainteresowanie tą metodą wynika z jej wysokiej dokładności, szybkości uzyskiwania wyników identyfikacji mikroorganizmów, stosunkowo niskiego kosztu analiz i prostej implementacji do laboratoriów diagnostycznych [15,49]. Niemniej jednak w literaturze naukowej dostępnych jest tylko kilka doniesień oceniających zastosowanie MALDI-TOF MS do identyfikacji dermatofitów [5,10,23,32,40,49,50] Celem niniejszej pracy jest dokonanie przeglądu piśmiennictwa traktującego o zastosowaniu techniki MALDI-TOF MS w diagnostyce dermatomykoz, ze szczególnym uwzględnieniem identyfikacji dermatofitów. Ponadto, w niniejszej pracy opisane są zalety i ograniczenia tej techniki w implementacji do rutynowego stosowania w laboratoriach mykologicznych.…”
Section: Wprowadzenieunclassified